PERANCANGAN SISTEM OTOMATISASI CONTROL MOTOR 3 PHASE MENGGUNAKAN BLUETOOTH BERBASIS ARDUINO UNO - Syarif Moh Rofiq Al- Ghony, Subuh Isnur Haryudo, Jati Widyo Leksono (Reaktom : Rekayasa Keteknikan dan Optimasi, 2019)
The electric motor is a device that serves to transform electrical energy into mechanical energy of motion. In this case the designed control system motor 3 phase by Smartphones through bluetooth network to find out the effective range of extremity. The methods used in the form of data capture of measurement effective range the furthest that can be reached by bluetooth to activate relay SPDT and motor 3 phase. Results of testing the most effective distance of the otomasisasi control system of motor 3 phase maximum as far as 15 meters with a time of pause 0.5 seconds.